Wildland : the making of America's fury - Osnos, Evan, 1976- (Farrar, Straus and Giroux, 2021)
"After a decade abroad, the National Book Award--and Pulitzer Prize--winning writer Evan Osnos returns to three places he has lived in the United States-Greenwich, CT; Clarksburg, WV; and Chicago, IL--to illuminate the origins of America's political fury"--